Inventions : discover some of the amazing technology of the past, with more than 20 fun and fascinating projects - Halstead, Rachel; Reid, Struan (London : Southwater, 2008)
Contains illustrated instructions for over twenty projects that teach about the history of technology and includes background information about teach topics.
Includes index.
6.6
3-6
Keywords: Handicraft -- Juvenile literature; Inventions -- History -- Juvenile literature; Handicraft; Inventions -- History; Handicraft; Inventions -- History